Conservation agriculture: Implementation guidance for policymakers and investors - Richards, Meryl B.; Sapkota, Tek Bahadur; Stirling, Clare M.; Thierfelder, Christian L.; Verhulst, Nele; Friedrich, T; Kienzle, J (2014)
Conservation agriculture (CA) can increase resilience to climate change and has the potential to contribute to climate change mitigation. The benefits of CA are highly site- specific. Innovative approaches are needed to overcome barriers for uptake of CA by smallholders.